Clinical and Radiographical Evaluation of Non-syndromic Dental Anomalies in Turkish Children - Karataban, Pinar Kiymet; Zorlu, Sevgi; Ozdas, Didem Oner (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: The aim of this study was to investigate the frequency and distribution of non-syndromic developmental dental anomalies in Turkish children in different age groups. SUBJECTS AND METHODS: A sample of 516 children aged 3–17 years who attended the Pediatric Dentistry Department of Istanbul Aydin University were evaluated clinically and radiographically for the existence of any structural, shape, and number anomalies of the developing dentition, and the most prevalent anomalies were compared according to gender and age groups. RESULTS: The most observed dental anomaly was Molar Incisor Hypomineralization (MIH) and tooth agenesis by a percentage of 14.3% and 4.8%, respectively. The incidence of MIH was higher in 7–8 and 9–10 years of age groups. There were no anomalies detected in 361 (70%) of the patients; meanwhile, only one anomaly was observed in 110 (21.3%), two different anomalies at the same time were observed in 33 (6.4%), and more than two anomalies were observed in 12 (2.3%) in the study group. STATISTICS: The statistical analysis of the results was obtained using the IBM SPSS Statistics 22 (IBM SPSS, Inc USA) program. p < 0.05 was considered to be statistically significant. CONCLUSION: Although there are no known systemic disturbances, at least, one dental anomaly was observed in 21.3% of the children. The most observed anomalies were MIH and tooth agenesis. An increase in the MIH prevalence throughout the world may lead to the suggestion that more investigations should be made on environmental predisposing factors. Besides, there might be common genetic factors and genes (PAX9, AXIN2, MSX1) affecting both tooth development and tumor formation which may be a potential risk marker for future cancer development.